Determination of Organophosphorus Pesticides in Vegetables by Solid-Phase Extraction Cleanup and Gas Chromatography - Chai, Alvin Lian Kuet; Lau, Seng (Universiti Putra Malaysia Press, 2003)
A simple and rapid gas chromatography method has been developed for simultaneous determination of organophosphorus pesticides in vegetables. Residues are extracted with acetone and dichloromethane. Extracts are cleaned up by a mixed-mode solid-phase extraction column, quaternary amine and aminopropyl silane. The pesticides are determined by gas chromatography using a flame photometric detector. The recoveries for 9 pesticides in three vegetables: carrot, cucumber and green mustard, fortified at 0.5 mg/kg were in the range of 80.3% to 115.0%. Lower recoveries were obtained for methamidophos and dimethoate. The results were compared to the method currently used in the laboratory which does not include any cleanup.